Peran Unit Kegiatan Mahasiswa (UKM) Dan Konsep Kepemimpinan Terhadap Pengembangan Diri Mahasiswa FEB UTM - Ameyla Nadhira Tsurayya; Renda Febriana; Muhammad Alkirom Wildan (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Bina Insani, 2024)
This research aims to examine the role of Student Activity Units (UKM) at the Faculty of Economics and Business, University of Trunojoyo Madura (FEB UTM), in the personal development of students, as well as analyze the impact of leadership styles implemented within UKM on this process. In the context of higher education, student development has become increasingly important, given the demands of the job market, which prioritize not only academic abilities but also interpersonal and leadership skills. This research uses a quantitative method with regression analysis to evaluate the relationship between participation in UKM, leadership style, and student personal development. The findings indicate that participation in UKM has a significant positive impact on the development of non-academic skills such as leadership, communication, and self-management. Furthermore, the transformational leadership style applied by UKM administrators proves effective in empowering members, enhancing motivation, and encouraging both personal and professional growth. This research fills the gap in the literature regarding the contribution of UKM within FEB UTM and provides insights for UKM managers, campus administrators, and students about the importance of involvement in student organizations. Therefore, this research recommends the development of more effective programs to enhance students' non-academic skills through UKM. Keywords: Student Activity Unit, Leadership, and Personal Development.